HUBUNGAN PENGETAHUAN PERAWAT TENTANG TRIASE TERHADAP KETEPATAN LABELING TRIASE - Nety " Elvia; Sofiana " Nurchayati; Ganis " Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract  Triage system is a selection system of patient election for determine criticalness levels and patient priority handling, a factor that very important is knowledge. By nurse we can see accuration labelling can we seen from conformity valuation triage with label that given with use The Australian Skill Triage (AST) valuation. The purpose of this research was to know the relationship of nurse’s knowledge about to triage labeling in Emergency Department (ED) at Arifin Achmad General Hospital Pekanbaru. This reaserch design was descriptive correlation with cross sectional study. Samples in this research were 36 nurses taken by total sampling technique. The instrument applied was a questionnaire about knowledge adc accuracy labeling (p value 0,532-0,854). This research used univate analysis to know distribution of frequencies and bivariate analysis by using chi square test. The conclution of this research showed there was no correlation between nurse knowledge with accuracy labeling that p value (1,000) > α (0,05). Recomendation from reasearcher is the nurse in emergency department must be upgrade their knowladge about triage and more participate in emergency exercise.  Keywords              : knowledge, labeling, nurse, triage